effectiveness Of A Play-style Learning Programme To Modify Hypermobility And Distraction For Primary School Pupils - قاضي محمد; ربوح صالح (University of Eloued جامعة الوادي, 2024)
ملخص البحث: تهدف الدراسة إلى التعرف على مدى تأثير برنامج بطريقة اللعب في التقليل من أعراض اضطراب فرط الحركة وتشتت الانتباه للتلاميذ المرحلة الابتدائية، حيث استخدم الباحث المنهج التجريبي في دراسته على عينة قصدية مكونة من 24 تلميذ موزعة على مجموعتين تجريبية وضابطة واستخدم الباحث وحدات تعليمية أدرج فيها الألعاب الصغيرة والشبه رياضية في المرحلة التحضيرية بالنسبة للمجموعة التجريبية إما المجموعة الضابطة مارست النشاط البدني بشكل عادي ، واستخدم استبيان أعراض فرط الحركة وتشتت الانتباه والاندفاعية الموجهحيث خلصت الدراسة إلى: أنه هناك تأثير لبرنامج بطريقة اللعب في حصة التربية البدنية بنسختيه للأولياء وأساتذة المدرسة الابتدائية ، وعولجت المعطيات بواسطة برنامجوالرياضية في التقليل من أعراض اضطراب فرط الحركة وتشتت الانتباه لدى التلاميذ تم رصده من خلال الاستبيان الموجه للأسرة و الاستبيان الموجه لأستاذ المدرسة الابتدائية . Abstract: The study aims to identify the impact of the gameplay program on reducing ADHD symptoms and distracting pupils at the primary level, where the researcher used the experimental curriculum in his study on an intentional sample of 24 pupils spread across two experimental groups The researcher used educational modules in which small and semi-athletic games were included in the preparatory phase for the pilot group either the control group exercised normal physical activity, used a questionnaire of hypermobility and distraction symptoms and impulsivity directed at its versions to parents and physical education professors, and the data were processed by the SPSS programme, where the study concluded: The gameplay program in the Physical and Sports Education class has the effect of reducing the symptoms of ADHD and distracting pupils, which was monitored through the family-oriented questionnaire and the primary school professor's questionnaire.
Keywords: اضطراب فرط الحركة وتشتت الانتباه; الطور الابتدائي